Modulating SEI formation via tuning the solvation sheath for lithium metal batteries. Issue 70 (17th August 2022) - Sun, Seho; Kim, Gaeun; Lee, Dongsoo; Park, Eunkyung; Myeong, Seungcheol; Son, Byoungkuk; Lee, Kangchun; Jang, Minchul; Paik, Ungyu; Song, Taeseup
Abstract : Water-induced solvation sheath control enables higher efficiency of Li metal usage, resulting from novel anion-derived SEI layer formation. Abstract : The solvation sheath of Li + –glyme was modulated to enhance Li + –TFSI − association by adopting a highly polar solvent, especially water molecules, which affects the solid electrolyte interface (SEI) layer composition. By the Li + –TFSI − association, a TFSI − anion-derived SEI layer is formed on the Li metal anode, resulting in higher Li metal anode efficiency.